Confier et dire la vérité : pour réussir une communauté politique de production du lien éthique dans la relation pédagogique - Silvio Gallo; Alexandre Filordi de Carvalho (Nantes Université, 2018)
This paper aims to problematize the theme of trust in the pedagogical relationships established in schools, and it does so by taking as a central one the notion of parrhesia, proposed by Michel Foucault based on the study of ancient Greek texts. Such concept is presented and commented on from the last courses of Foucault, but also with the aid of a contemporary reading proposed by Maurizio Lazzarato in recent works, which mainly problematizes the ethical and political aspects of the parrhesia. In the field of pedagogical relations, the effects of "telling the truth" are problematized and how new ethical bonds and new relations of trust (in oneself and in others) are generated from such parrhesiastic acts. Thinking parrhesia and its effects, sometimes Foucault has mentioned the figure of the teacher; in this article, the telling the truth is thought from the point of view of the students, in order to understand the effects it produces in the processes of subjectivation.